Expression profiling and characterization of cold, freezing-related genes from Brassica rapa cultivars. Issue 2 (2nd April 2016) - Thamilarasan, Senthil Kumar; Park, Jong-In; Jung, Hee-Jeong; Chung, Mi-Young; Cho, Yong-Gu; Nou, Ill-Sup
Abstract : Brassica is a very important vegetable group worldwide. Cold and freezing stress are the major environmental factors that limit the productivity of Brassica. In this study, we retrieved 903 stress-chilled unigenes and the unique transcripts were classified functionally using gene ontology (GO) hierarchy, Kyoto Encyclopedia of Genes and Genomes (KEGG). KEGG orthology and structural domain data were obtained from the biological database to the unigene data set. Unigene data sets provide a wide outlook of functional characterization of Brassica rapa. In silico analysis revealed 94.2% of unigenes to be well annotated toward Reeds one-dimensional concept. On the basis of similarity searches and GO annotation of biological process (BP), 139, 113, and 57 sequences showed a response to stress (SR), abiotic stimulus (AS), and biotic stimulus (BS), respectively. To validate this observation, seven unigenes were randomly selected from AS that are known to be associated with cold stress from previous studies in other species and these genes were examined by real-time polymerase chain reaction to understand the change in expression pattern under cold and freezing stress. In silico study of occurrence in the AS subcategory revealed the presence of 138 single sequence repeats, some of which are being explored to assess genetic diversity among B. rapa . Thus, the unigene data set provides valid resources for discovering the potential genes related to cold and freezing resistance in B. rapa cultivars, and can be useful resources for genetic engineering of Brassica sp.